Development and Evaluation of Multifunctional Co-Processed Excipients for Fast Dissolving Tablet Formulation - Amar M. Raval; Pandya Foram Utpalkumar; Pandya Vipra Utpalkumar; Bhavsar Prathmesh Ratnakar (Asian Journal of Pharmaceutical Research and Development, 2026)
Fast dissolving tablets (FDTs) are novel oral solid dosage forms designed to disintegrate rapidly in saliva without the need for water. They improve patient compliance, especially in pediatric, geriatric, and dysphagic patients. The present study aimed to formulate and evaluate co-processed excipients for fast dissolving tablets using the wet granulation method. Different batches of co-processed excipients were prepared using Crospovidone, microcrystalline cellulose, sodium starch glycolate, mannitol, talc, magnesium stearate, and PVP K30. Pre-compression parameters such as bulk density, tapped density, Carr’s index, Hausner ratio, and angle of repose were evaluated to determine flow properties. Post-compression studies included hardness, disintegration time, wetting time, and water absorption ratio. The results demonstrated that co-processed excipients significantly improved the flowability and compressibility compared to physical mixtures. Among all formulations, batch F5 showed optimum performance with excellent flow properties, compressibility, rapid disintegration time (40.58 sec), and wetting time (26 sec). The study concluded that co-processed excipients are an effective approach for improving the overall performance of fast dissolving tablets.